Exploring the Role of Islamic Religious Education in the Crisis of Character and Morality in the Modern Era - Rofik, Moh.; Nursyam; Takunas, Rusli; Naima; Rahayu, Fitri (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2026)
Character education in Indonesia faces serious challenges due to the decline of morals and character, such as student fights, bullying, and corruption, in the modern era. The purpose of this research is to analyze character formation through Islamic religious education (PAI) as the main solution. This research is qualitative with a type of library research and a descriptive-qualitative approach. Library research utilizes literature sources such as books and journal articles as the main data, which is collected, read, understood, and analyzed in depth and systematically. The data analysis technique uses descriptive analysis through a deductive approach to describe the data objectively and draw conclusions from general theories to specific cases according to the focus of the research. The results show that Islamic education is needed in supporting character formation in the modern era which is full of challenges faced by students today. Through Islamic religious education, students can have the opportunity to form individuals of faith, character, morality, responsibility, and dignity, through the function of development, improvement, and filtering of cultural values. Islamic religious education is one of the main foundations in building noble character in harmony with human nature and providing direction on how to behave. Abstrak: Pendidikan karakter di Indonesia menghadapi tantangan serius akibat penurunan moral dan karakter, seperti perkelahian mahasiswa, perundungan, dan korupsi, di era modern. Tujuan dari penelitian ini adalah untuk menganalisis pembentukan karakter melalui pendidikan agama Islam (PAI) sebagai solusi utama. Penelitian ini bersifat kualitatif dengan jenis penelitian perpustakaan dan pendekatan deskriptif-kualitatif. Penelitian perpustakaan memanfaatkan sumber literatur seperti buku dan artikel jurnal sebagai data utama, yang dikumpulkan, dibaca, dipahami, dan dianalisis secara mendalam dan sistematis. Teknik analisis data menggunakan analisis deskriptif melalui pendekatan deduktif untuk mendeskripsikan data secara objektif dan menarik kesimpulan dari teori umum hingga kasus spesifik sesuai dengan fokus penelitian. Hasil penelitian menunjukkan bahwa pendidikan Islam sangat dibutuhkan dalam mendukung pembentukan karakter di era modern yang penuh dengan tantangan yang dihadapi oleh mahasiswa saat ini. Melalui pendidikan agama Islam, siswa dapat memiliki kesempatan untuk membentuk individu yang beriman, berakhlak, bermoral, bertanggung jawab, dan bermartabat, melalui fungsi pengembangan, peningkatan, dan penyaringan nilai-nilai budaya. Pendidikan agama Islam merupakan salah satu landasan utama dalam membangun karakter mulia yang selaras dengan sifat manusia dan memberikan arahan bagaimana berperilaku.